Self-Esteem and Defense Mechanisms in HIV-Positive and AIDS Patients - Baykara, Sema; Tartar, Ayşe Sağmak; Korucu, Tuba; Korkmaz, Sevda; Atmaca, Murad; Akbulut, Ayhan (Physicians Postgraduate Press Inc., 2020)
Objective: To investigate the self-esteem and defense mechanisms in patients diagnosed with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS). Methods: This prospective, cross-sectional study included 29 patients diagnosed with HIV/AIDS admitted to inpatient or outpatient clinics between March 2018 and January 2019 and 29 healthy subjects. Participants were assessed using a sociodemographic and clinical data form, the Rosenberg Self-Esteem Inventory (RSEI), the Defense Style Questionnaire (DSQ), and the Beck Anxiety Inventory (BAI). Results: Patients with HIV/AIDS had significantly higher scores on the fantasy, psychosomatic symptoms, and parental interest subscales of the RSEI. There was no significant difference between the groups on the other subscales, including the self-esteem subscale. There was no correlation between the duration of the disease and self-esteem. The neurotic defense mechanism and immature defense mechanism subscale scores of the DSQ were significantly higher in the HIV/AIDS group compared to the control group (P < .01). Undoing and reaction formation scores in neurotic defense mechanisms and projection, devaluation, autistic fantasy, and splitting scores in immature defense mechanisms were significantly higher in the HIV/AIDS group compared to controls (P < .05). There was no significant difference between the groups based on the mature defense mechanisms subscale scores. Conclusions: No difference was found in the self-esteem scores of the HIV/AIDS and control groups, and this finding could be associated with the stability of the self-esteem concept. It was also determined that patient group members utilized neurotic and immature defense mechanisms more often compared to the healthy group, and there was no difference between the groups based on mature defense mechanisms. © 2020 Physicians Postgraduate Press, Inc.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Cross-Sectional Studies; Defense Mechanisms; Female; HIV Infections; Humans; Male; Middle Aged; Prospective Studies; Self Concept; acquired immune deficiency syndrome; adult; cross-sectional study; defense mechanism; female; human; Human immunodeficiency virus infection; male; middle aged; prospective study; psychology; self concept